MVP predicts the pathogenicity of missense variants by deep learning - Hongjian Qi (Nature Portfolio, 2021)
Accurate prediction of variant pathogenicity is essential to understanding genetic risks in disease. Here, the authors present a deep neural network method for prediction of missense variant pathogenicity, MVP, and demonstrate its utility in prioritizing de novo variants contributing to developmental disorders.